Los Festivales de Oposición Kultur- und Reformpolitik der Mexikanischen Kommunistischen Partei auf den Festivales de Oposición (1977-1981) - Abu Chouka, Sherin (Historamericana, 2022)
Sherin Abu Chouka examines the Festivales de Oposición of the Mexican Communist Party (PCM), which between 1977 and 1981 developed into an international networking platform and a meeting place for politicized art of the Canto Nuevo Latinoamericano.